IMPLEMENTASI PERATURAN DAERAH OGAN KOMERING ILIR (OKI) NOMOR 9 TAHUN 2008 TERHADAP PENGELOLAAN PERAIRAN UMUM DARATAN - Radityo Pramoda (Jurnal Borneo Administrator, 2011)
This research aims to review the implementation of the new provisions of Local Regulation No. 9/2008, about the Management of Lebak, Lebung, and Rivers in Ogan Komering Ilir, which has become the autonomous village, and knowing how it works. Analysis of the research was conducted by using descriptive exploratory method, through qualitative approach, supported by primary and secondary data. The results show, that policy transformation of the management of inland waters by enactment of Local Regulation No. 9/2008, has provided greater access to the community to utilize the fish resources; the authority of the village to arrange lebak, lebung, and river is becoming much wider; the less optimal implementation of Local Regulation No. 9/2008, is caused by the apparatus and community who are not ready yet to adopt the value change and new norms. Keywords: implementation of local regulation, management, inland water.Penelitian ini bertujuan untuk mengkaji implementasi ketentuan baru Perda OKI No. 9/2008, tentang Pengelolaan Lebak, Lebung, dan Sungai dalam Kabupaten Ogan Komering Ilir, yang menjadi otonomi desa serta mengetahui pelaksanaannya. Analisa penelitian menggunakan metode deskriptif eksploratif, melalui pendekatan kualitatif, yang didukung data primer dan sekunder. Hasil penelitian menunjukkan, bahwa transformasi kebijakan pengelolaan perairan umum daratan dengan berlakunya Perda OKI No. 9/2008, memberikan akses yang lebih besar kepada masyarakat untuk memanfaatkan sumber daya ikan; kewenangan yang dimiliki desa menjadi lebih luas dalam mengatur lebak, lebung, dan sungai; kurang optimalnya implementasi Perda OKI No. 9/2008, dikarenakan aparatur dan masyarakat Desa Berkat belum siap mengadopsi perubahan nilai serta norma baru.Kata kunci: implementasi Perda, pengelolaan, perairan umum daratan.